Modifikasi Kunci Kontak Menggunakan Perintah Suara (Arduino Uno R3) Pada Sepeda Motor - Indra Hasan; Denur; Reky Zukriady (Jurnal Surya Teknika, 2020)
Motorcycles are the most in demand vehicles in Indonesia. The number of users of these two-wheeled vehicles continues to increase every year. However, the increasing number of motor vehicles is also accompanied by increasing crimes against motorcycle users. To solve the problem, it is designed a security tool on motorcycles that can turn motorcycles on and off using voice commands based on arduino uno r3 connected to bluetooth on smartphones. It aims to tackle and reduce the number of crimes against motorcycle users.